Proceedings of the 2019 2nd International Conference on E-Business, Information Management and Computer Science 2019
DOI: 10.1145/3377817.3377838
|View full text |Cite
|
Sign up to set email alerts
|

E-Marketplace Acceptance of MSMEs in Bali Based on Performance Expectancy and Task Technology Fit

Abstract: Micro, Small, and Medium Enterprises (MSMEs) plays an important role in a country's economic growth especially in those developing countries. Nonetheless for this industry to continue grow and sustain, entrepreneurs need to be actively involved in emarketplace as many consumers now prefer to do online purchases or transactions since it is convenient. Thus, this paper aimed to study the e-marketplace acceptance in terms of performance expectancy and task technology fit by the entrepreneurs in selected provinces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 9 publications
1
10
0
Order By: Relevance
“…Studies show a significant link between PE and e-commerce adoption (Venkatesh et al, 2003). The impact of PE on EM adoption has also been scrutinized (Wang et al, 2006;Büyüközkan, 2004;Subawa et al, 2019;Wijaya & Handriyantini, 2020). According to Wang et al, (2008), increased PE is associated with a stronger behavioural intention to utilize EM.…”
Section: Performance Expectancy (Pe)mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show a significant link between PE and e-commerce adoption (Venkatesh et al, 2003). The impact of PE on EM adoption has also been scrutinized (Wang et al, 2006;Büyüközkan, 2004;Subawa et al, 2019;Wijaya & Handriyantini, 2020). According to Wang et al, (2008), increased PE is associated with a stronger behavioural intention to utilize EM.…”
Section: Performance Expectancy (Pe)mentioning
confidence: 99%
“…FC is defined as the seller's perception of the availability of resources and assistance in utilizing technology (Davis, 1989;Yu, 2012). FC is critical in that it influences the adoption of e-commerce Mzee et al, 2015;Subawa et al, 2019). Factors that support EM are: familiarity with online business processes and well-developed technical infrastructure, which are included in this construct (Prihastomo et al, 2018).…”
Section: Facilitating Condition (Fc)mentioning
confidence: 99%
“…The involvement of third parties in the procurement of electoral infrastructure and campaigns in particular mostly came from small-scale entrepreneurs. Subawa & Mimaki (2019) in their research found that micro, small and medium enterprises (MSMEs) play an important role in various sectors, including the role in procuring campaign props. Based on the author's observations, the community movement to campaign for the existence of empty boxes has not been included on social media.…”
Section: Campaign Dynamics Of One Candidate Pairmentioning
confidence: 99%
“…Strictness in selecting prospective franchise buyers, conducted with conventional methods, and familiarising with the buyer characteristics, is not entirely performed online. Subawa and Mimaki (2019) examined micro, small and medium enterprises (MSMEs) based on the importance of small business implementation and information technology in developing markets through emarkets. Brochado et al (2018) stated that local brand franchises' development is a mixture of traditional and instant business patterns.…”
Section: Instant Cultural Responsementioning
confidence: 99%